The influence of the quality of tax examiners, the integrity of tax examiners and the ratio of tax examiners on taxpayer compliance - Aloisius Hama (Institute of Accounting Research and Novation (IARN), 2022)
The purpose of this study was to determine the effect of Tax Auditor Quality, Tax Auditor Integrity and Tax Auditor Ratio on taxpayer compliance at KPP Pratama Surabaya Mulyorejo. The population in this study were the Examination section employees as respondents. The analytical model used in this study is Multiple Linear Regression. This analysis model was chosen because this study was designed to examine the effect of the independent variables on the dependent variable. Based on the analysis and discussion that has been carried out, the following conclusions can be drawn: The Need for Tax Auditor Quality, Tax Auditor Integrity and Tax Auditor Ratio simultaneously influence Taxpayer Compliance. Tax Auditor Quality Needs.